Bioprocess Development for Lantibiotic Ruminococcin-A Production in Escherichia coli and Kinetic Insights Into LanM Enzymes Catalysis - Ongey, Elvis L.; Santolin, Lara; Waldburger, Saskia; Adrian, Lorenz; Riedel, Sebastian L.; Neubauer, Peter (Frontiers in Microbiology, 2019)
Ruminococcin-A (RumA) is a peptide antibiotic with posttranslational modifications including thioether cross-links formed from non-canonical amino acids, called lanthionines, synthesized by a dedicated lanthionine-generating enzyme RumM. RumA is naturally produced by Ruminococcus gnavus, which is part of the normal bacterial flora in the human gut. High activity of RumA against pathogenic Clostridia has been reported, thus allowing potential exploitation of RumA for clinical applications. However, purifying RumA from R. gnavus is challenging due to low production yields (< 1 µg L-1) and difficulties to cultivate the obligately anaerobic organism. We recently reported the reconstruction of the RumA biosynthesis machinery in Escherichia coli where the fully modified and active peptide was expressed as a fusion protein together with GFP. In the current study we developed a scale-up strategy for the biotechnologically relevant heterologous production of RumA, aimed at overproducing the peptide under conditions comparable with those in industrial production settings. To this end, glucose-limited fed-batch cultivation was used. Firstly, parallel cultivations were performed in 24-microwell plates using the enzyme-based automated glucose-delivery cultivation system EnPresso® B to determine optimal conditions for IPTG induction. We combined the bioprocess development with ESI-MS and tandem ESI-MS to monitor modification of the precursor peptide (preRumA) during bioreactor cultivation. Dehydration of threonine and serine residues in the core peptide, catalyzed by RumM, occurs within 1 h after IPTG induction while formation of thioether cross-bridges occur around 2.5 h after induction. Our data also supplies important information on modification kinetics especially with respect to the fluctuations observed in the various dehydrated precursor peptide versions or intermediates produced at different time points during bioreactor cultivation. Overall, protein yields obtained from the bioreactor cultivations were >120 mg L-1 for the chimeric construct and >150 mg L-1 for RumM. The correlation observed between microscale and lab-scale bioreactor cultivations suggests that the process is robust and realistically applicable to industrial-scale conditions.